Review: Julie Knight, John Lever and Andrew Thompson. 2017. Labour, Mobility and Temporary Migration. A Comparative Study of Polish Migration to Wales - Rosiak, Karolina (Studia Celtica Posnaniensia, 2018)
Review: Julie Knight, John Lever and Andrew Thompson. 2017. Labour, Mobility and Temporary Migration. A Comparative Study of Polish Migration to Wales. Cardiff: University of Wales Press. 260 pages. ISBN: 978-1-78683-0807. Review by KAROLINA ROSIAK, Adam Mickiewicz University in Poznań